Rota sustentável dos resíduos de construção e demolição oriundos das obras de pequenos geradores: uma proposta para o município de São Carlos - SC - Alberici, Debora Fatima (2017)
Irregular provisions of construction and demolition waste (CDW) are now found in the various brazilian municipalities, which are mostly due to small works or informal reforms. This condition becomes even more recurrent in small municipalities, which do not have CDW management effectively in operation under the brazilian legislation, thus not offering adequate disposal and disposal options for these materials. Improving rcd management, besides being an effective tool for its management, is one of the strategies to reduce the associated environmental impacts. In view of the above, this research aims to propose a sustainable route for construction and demolition waste (CDW) from the works of small generators in the municipality of são carlos / sc. Through the characterization of the municipality about the CDW; mapping of the current flow of CDW management processes from small generators; identification of the ideal flow of processes for the management of CDW from small generators; indication of changes necessary to the municipality to adapt the existing current flow to the ideal flow and presentation to the public power of an efficient study on the flow of the CDW, pointing out solutions regarding the destination or final disposal. This research was carried out based on theoretical studies already done on CDW, current legislation and project management tools, published in scientific articles, dissertations, theses and books. As a result, we obtained the ideal flow, named in this work as sustainable CDW route. The ideal flow made it possible to visualize that the small generators do not have an environmentally correct option to dispose of their CDW, that the municipal integrated solid waste management plan (MISWMP) does not contemplate the procedures pertinent to the management of the CDW and needs to pass an update, which the municipal legislation should be changed to suit the updated MISWMP, that all this information should reach the community through environmental education that should be effective and continuous and that there should be the inspection to align: federal legislation>MISWMP> municipal legislation> environmental education > concrete and environmentally sound actions. It is concluded that this research has brought useful information to the municipality of São Carlos, and that if this information is disseminated, it will certainly result in environmental and social benefits for this municipality and its region.